G158 Recruiting Ethnic Minority Participants to a Clinical Trial: Qualitative Study. (4th June 2013) - Nwokoro, C; MacNeill, V; Griffiths, C; Grigg, J; Seale, C
Abstract : Objectives: To compare the motives and experiences of different ethnic groups participating in a randomised double blind placebo-controlled trial of montelukast in preschool wheeze, and to assess parents' or guardians' understanding of trial procedures and their implications, including the collection of genetic material. Design: qualitative interviews with parents or guardians. Setting: Parents of children recruited following medical attendance with wheeze were interviewed in their homes. Participants: 42 parents, (20 of Bangladeshi origin, 10 white UK, 12 other ethnicities). Results: Anxiety related to wheezing was a common primary motive for trial enrolment. Parents viewed the trial as a route to improved treatment. Verbal delivery of trial information was more effective than study literature, especially for Bangladeshi families, with low parental literacy and high levels of trust in medical professionals contributing to this effect. All ethnic groups expressed a low understanding and/or retention of essential study concepts such as randomisation and genetic testing. Conclusions: Bangladeshi families are particularly motivated to participate in clinical trials despite variable comprehension of study concepts. This motivation is more strongly contingent on strong researcher-subject rapport than on the quality of study literature. Trial teams seeking to recruit from South Asian populations should emphasise face-to-face verbal explanation of trial concepts and procedures and consider modified trial literature.